2014
DOI: 10.1590/1516-3180.2014.1324710
|View full text |Cite
|
Sign up to set email alerts
|

Perineal trauma after vaginal delivery in healthy pregnant women

Abstract: CONTEXT AND OBJECTIVE: Despite all the medical care provided during delivery labor, perineal injury is still prevalent and may lead to diverse pelvic floor disorders. The aim here was to investigate the prevalence of obstetric and anal sphincter injuries (OASIS) in healthy pregnant women after vaginal delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0
9

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 34 publications
3
12
0
9
Order By: Relevance
“…The results of the study depicted a high prevalence of perineal trauma. The findings were consistent with findings of a similar study carried out by Oliveira et al, (2014). The findings were also similar with those by Melamed et al, (2013), where the prevalence of 3 rd and 4 th degree tears was 0.6% and 3 rd degree tears were more common than 4 th degree.…”
Section: Discussionsupporting
confidence: 92%
“…The results of the study depicted a high prevalence of perineal trauma. The findings were consistent with findings of a similar study carried out by Oliveira et al, (2014). The findings were also similar with those by Melamed et al, (2013), where the prevalence of 3 rd and 4 th degree tears was 0.6% and 3 rd degree tears were more common than 4 th degree.…”
Section: Discussionsupporting
confidence: 92%
“…In a study conducted in São Paulo, the infusion rates were 31% in the dilation stage and 25.8% in the expulsion stage (12) . In Ribeirão Preto, it was found that the use of oxytocin in the active labor phase was not a risk factor for first-and second-degree tears (13) . The use of this medication in this study indicates rational use in accordance with the institution's protocol, recommended for achieving the ideal uterine dynamics for each pregnant woman, without any negative repercussions on perineal outcome.…”
Section: Discussionmentioning
confidence: 96%
“…In a maternity hospital in Rio de Janeiro (RJ), the rate of this procedure was 27.38% (5) , similar to the findings of the present study. In a study with 3,034 pregnant women who had full-term pregnancies, in Ribeirão Preto (SP), there was an unusual finding: the rupture of membranes 12 to 18 hours before the birth reduced the risk of perineal tears by almost 50% (13) . This association was not manifested in the data in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…A reparação cirúrgica inadequada pode afetar a prevalência de trauma nas mulheres durante o período pós-parto. A equipe de saúde necessita ter um olhar atento ao atendimento à mulher e tomar medidas profiláticas o quanto antes como, por exemplo, indicar o uso de cremes que melhoram a aparência e o aspecto da cicatriz, caso o resultado final não tenha sido como o desejado (24) . Evidências científicas mostram que o relacionamento sexual da mulher após a episiotomia, por vezes, torna-se um desafio, pois além de poder causar a dispareunia, alterações anatômicas e hematomas, pode também afetar negativamente a sua autoestima e o relacionamento sexual com o seu parceiro (18) .…”
Section: Se Desse Pra Ser Vista Com Biquíni Com Certeza"(lírio)unclassified